PENGARUH KEPEMIMPINAN TRANSFORMASIONAL MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN (KOP “SAE” Pujon Malang Jawa Timur) - Rista Yuli Diah Saputri; Hadi Sunaryo (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this study was to describe transformational leadership, motivation, work culture and employee performance and to determine the effect of transformational leadership, motivation and work culture on employee performance partially and simultaneously.This research method uses quantitative methods. This type of research is explanatory research.The sample of this study was the "SAE" Pujon Malang KOP employee using the Porpotional Random Sampling technique, which was 77 respondents. Data collection methods use questionnaires or questionnaires. The analytical method used in this study is multiple regression analysis with SPSS 14.0 for Windows.The results of this study indicate that transformational leadership and work culture affect employee performance, while motivation has no influence on employee performance. Simultaneously transformational leadership, motivation and work culture influence the performance of KOP employees "SAE" Pujon Malang East Java. Keywords:Transformational Leadership, Motivation, Work Culture and Employee Performance.